Customizing solutions: an internship journey in ABAP SAP development and custom reporting at Eitekh ERP LTD - Chowdhury, Raiyan Nazir (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.